Amazonian indigenous settlement and local development in Pastaza, Ecuador - Ruth I. Arias-Gutiérrez; Angelina Herrera Sorzano; Roberto González Sousa (Universidad de La Habana, 2016)
In six Amazonian indigenous communities that call to their selves as membership of nación Kichwa, located in Pastaza province, in Ecuador, it is analyzed the process of inhabitation, population characteristics, how much the territory is enough for food requirements for the indigenous families, and their use of land, to determine important factors to improve strategies for local sustainable development. It is considered important because Ecuador has constitutional protection for plural ethnicity and it is looking for improving a new productivity matrix that let down extraction and contamination and raise another matrix based on knowledge and richness from natural renewable resources. Survey used statistics information, qualitative analysis around reality in process, participant research, documentary analysis, oral history and surveys to leadership and family`s chiefs. Results confirm that communities hold standing their identity and knowledge systems of the Amazonian environment, whose conservation they need. Those are factors to be included in local development strategies that let people become safe from effects of extractives activities that are dangerous for culture and environment, in the geographic and biological diversity of the high Ecuadorian Amazonia.